The synthesis of the rhamnogalacturonan II component 3-deoxy-D-manno-2-octulosonic acid (Kdo) is required for pollen tube growth and elongation - Delmas, Frédéric (Journal of experimental botany, 2008)
Despite a very complex structure, the sugar composition of the rhamnogalacturonan II (RG-II) pectic fraction is extremely conserved. Among its constituting monosaccharides is the seldom-observed eight-carbon sugar 3-deoxy-D-manno-octulosonic acid (Kdo), whose phosphorylated precursor is synthesized by Kdo-8-P synthase. As an attempt to alter specifically the RG-II structure in its sugar composition and assess the consequences on the function of RG-II in cell wall and its relationship with growth, Arabidopsis null mutants were sought in the genes encoding Kdo-8-P synthase. Here, the isolation and characterization of one null mutant for the isoform 1 (AtkdsA1-S) and two distinct null mutants for the isoform 2 of Arabidopsis Kdo-8-P synthase (AtkdsA2-V and AtkdsA2-S) are described. Evidence is provided that AtkdsA2 gene expression is preferentially associated with plantlet organs displaying a meristematic activity, and that it accounts for 75% of the mRNAs to be translated into Kdo-8-P synthase. Furthermore, this predominant expression of AtKDSA2 over AtKDSA1 was confirmed by quantification of the cytosolic Kdo content in the mutants, in a variety of ecotypes. The inability to identify a double knockout mutant originated from pollen abortions, due to the inability of haploid pollen of the AtkdsA1- AtkdsA2- genotype to form an elongated pollen tube properly and perform fertilization